Análisis, diseño e implementación de un software de aprendizaje interactivo mediante la tecnología Kinect, orientado a los niños de 4 a 6 años de edad de la escuela fiscal mixta 24 de Junio de la ciudad de Machala en el año 2014. - Reyes González, Estefanía Elizabeth (2015)
The preliminary analysis carried out at the Joint Public School 24 June, it resulted in the emergence of the need to integrate new technology into classrooms, so it was considered developed as a solution "Design and implementation of an interactive learning software through Kinect technology, aimed at children 4 to 6 years of age Fiscal Primary school June 24, the city of Machala in 2014 "; allowing automation of topics of current curriculum of early education and First year of basic education by creating games operated by sensor, enabling to obtain a support tool to facilitate and improve the education of students by using resources current technology, which is the development of the project was carried out with the application of the Methodology software development RUP, this being the most suitable to provide business rules, consistent patterns of processes for the project team, minimize risks, deliver software quality and implement best practices in software development. The construction and implementation was performed with Visual Studio, specifically with Visual C #, as the programming platform that is predetermined by the Kinect sensor, complemented by the integration of a Manager Database in PostgreSQL, which allows better management data to be reliable, stable, with excellent performance and being free license software, which benefited in relation to cost issues. Thus learning software, cooperating to learning and use of technologies for better education, thus enabling be a support tool that supports the development of the student and also contributes to the advancement and innovation and contributes to the institution.